GIS-based quantitative assessment of desertification in Kebbi state, Nigeria - Aliero, Muhammadu Mansur; Ismail, Mohd Hasmadi (2016)
Desertification which has been a critical issue since time immemorial, however, has never been as it is at the present days. According to UNCCD, almost one third of the world agricultural land is facing one form of degradation or another. It causes adverse effects not only on the environment but also a severe economic, social and geopolitical consequence. There had been in place several international programs aimed to combat and mitigating the issue such as (UNEPA), (UNCCD), (UNFCCC-REDD+) etc. Other regional/national and local initiatives such as Korea-Mongolia greenbelt project, Niger-Nigeria trans-boundary ecosystem project, (NAPCD) in Nigeria, Afforestation programs etc. have also been implemented. However, the problem persists especially in the developing countries like Nigeria, mainly due poverty, deforestation, and unsustainable land management. Similarly these countries have limited capabilities to monitors, report and verify desertification effectively. Particularly, in Nigeria the extent and severity of desertification has not been fully establishes. This paper aimed at presenting desertification as a critical phenomenon and henceforth the need for application of geospatial technology and conventional inventories in monitoring its extent and severity in Kebbi state, Nigeria.